RANCANG BANGUN ALAT DESTILASI AIR LAUT MENGGUNAKAN TENAGA MATAHARI SEBAGAI ALTERNATIF PENYEDIAAN AIR BERSIH - Dewahastu Gaib; Asri Arbie; Dewa Gede Eka Setiawan (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2023)
Unfortunately, there has been a great worry about clean and healthy water for human consumption lately. Even though 2/3 of the earth's surface is covered by water, the access to safe water is only concentrated in certain areas. In Indonesia, water scarcity is increasing each year. Recent data on freshwater resources possessed by all countries in the world shows that Indonesia is ranked 51st with the highest risk of water scarcity (40-80%). There are several methods to gain access to safe water, one of which is the use of distillation equipment. This research aims to produce a design of freshwater distillation equipment from seawater by utilizing solar radiation towards the quantity of freshwater and to determine the quality of freshwater from the results of distillation which include water pH, salinity, and TDS tests. The research method is done by heating sea water in the distillation equipment using solar radiation. Findings reveal that the average solar intensity of 1608.25 (lux) and the ambient temperature of 38.5 °C can produce an average volume of freshwater of 336.75 ml per day from the incoming seawater volume of 2000 ml. The water quality produced has a pH of 6.5, a salinity of 0.2 ppt, and a TDS of 152 mg/L.